2020
DOI: 10.3390/foods9030353
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Application in the Wheat Booting Stage on Glutenin Polymerization and Structural–Thermal Properties of Gluten with Variations in HMW-GS at the Glu-D1 Locus

Abstract: Wheat gluten properties can be improved by the application of nitrogen. This study investigates the effects of nitrogen application in the booting stage on glutenin polymerization during grain-filling and structural–thermal properties of gluten based on the high-molecular-weight glutenin subunits (HMW-GSs) using near-isogenic lines (Glu-1Da and Glu-1Dd). The nitrogen rate experiment included rates of 0, 60, 90, and 120 kg N ha−1 applied with three replicates. Nitrogen significantly improved the grain quality t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…Application of N fertilizer increased GY as well as quality parameters such as GPC, SDS sedimentation values, and the dough properties FAB, DDT, and STA. These results are consistent with previous findings (Guarda et al 2004;Xue et al 2019;Song et al 2020). In contrast, negative effects were associated with the increased N level on baking properties such as Lfht, Tx, Soft, and Crcol.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Application of N fertilizer increased GY as well as quality parameters such as GPC, SDS sedimentation values, and the dough properties FAB, DDT, and STA. These results are consistent with previous findings (Guarda et al 2004;Xue et al 2019;Song et al 2020). In contrast, negative effects were associated with the increased N level on baking properties such as Lfht, Tx, Soft, and Crcol.…”
Section: Discussionsupporting
confidence: 93%
“…The effects of nitrogen fertilization on wheat quality have been extensively investigated (Guarda et al 2004;Xue et al 2019;Gagliardi et al 2020;Song et al 2020). In our study, a significant nitrogen effect was observed in several evaluated traits (Tables 2 and 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, RP-UPLC and 2D-DIGE analyses of the gliadin and glutenin subproteomes revealed that applying a large amount of high-N fertilizer (240 kg ha −1 ) significantly increased the accumulation of gliadin and glutenin components as well as the contents of storage proteins, implying improved dough viscoelasticity and bread quality [54]. The addition of N, expedited and enhanced the accumulation of total protein, glutenin, glu/gli ratio, HMW/LMW-GS, and GMP in the grain, raised the disulfide bond concentration, upgraded the secondary and microstructure of the gluten, and improved the thermal stability and dough mixing characteristics [55]. In recent decades, N fertilization of cereal crops has risen, having a significant impact on the amount and quality of storage proteins (gliadins and glutenins) and improved bread-making quality.…”
Section: Nitrogen Fertilizers: Substantially Affects Grain Yield and ...mentioning
confidence: 99%
“…However, few studies have considered the potential effects of the timing of N uptake and the role of late N fertilization, applied close to the ripening stages, on the accumulation of the different gluten protein fractions during grain filling [7]. In fact, the timing of the accumulation of the different gluten protein fractions during grain development seems to be fundamental to determine the structural-thermal gluten properties and the wheat quality, and thus to provide useful indicators of the technological quality of dough [16].…”
Section: Introductionmentioning
confidence: 99%